2019
DOI: 10.1038/s41598-019-43888-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genomic region(s) responsible for high iron and zinc content in rice

Abstract: Micronutrient especially iron and zinc-enriched rice hold immense promise for sustainable and cost-effective solutions to overcome malnutrition. In this context, BC 2 F 5 population derived from cross between RP-Bio226 and Sampada was used to localize genomic region(s)/QTL(s) for grain Fe (iron) and Zn (zinc) content together with yield and yield-related traits. Genotyping of mapping population with 108 SSR markers resulted in a genetic map of 2317.5 cM with an ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 27 publications
6
29
0
1
Order By: Relevance
“…In general, iron content showed lower variance and higher CV than zinc content. By contrast, previous works have shown that although iron and zinc contents are highly variable (Dixit et al, ), zinc content tends to be more consistent and less variable than iron content (Anuradha et al, ). This difference may be attributed to various environmental and genetic factors.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…In general, iron content showed lower variance and higher CV than zinc content. By contrast, previous works have shown that although iron and zinc contents are highly variable (Dixit et al, ), zinc content tends to be more consistent and less variable than iron content (Anuradha et al, ). This difference may be attributed to various environmental and genetic factors.…”
Section: Discussionmentioning
confidence: 78%
“…Grain iron and zinc contents are positively correlated (Anandan, Rajiv, Eswaran, & Prakash, ; Descalsota et al, ; Descalsota‐Empleo, Amparado, et al, ; Dixit et al, ; Inabangan‐Asilo et al, ; Stangoulis et al, ; Swamy, Descalsota, et al, ; Xu et al, ). Similarly, in this work, grain iron and zinc contents were positively correlated and presented similar correlations with other traits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Respective QTL References Zinc (Zn) qZN-5, qZN-7, qSZn2, qSZn12, qZn7, qZn3.1, qZn7.1, qZn7.2, qZn7.3, qZn12.1, qZn4, qZn6, qZn1-1, qZn12-1, qZn5-1, qZn8-1, qZn12-1, qZn2.1, qZn2.1, qZn3.1, qZn6.1, qZn6.2, qZn8.1, qZn11.1, qZn12.1, qZn12.2, qZn2.2, qZn8.3, qZn12.3, qZn3.1, qZn7, qZn8.3, qZn3-1, qZn1.1, qZn5.1, qZn9.1, qZn12.1, qZn1.1, qZn6.1, qZn6.2, qZn2-1, qZn2-2, qZn5, qZn10, qZn2.1, qZn3.1, qZn5.1, qZn5.2, qZn7.1, qZn9.1, qZn11.1, qZn 1.1, qZn2.1, qZn3.1, qZn3.2, qZn5.1, qZn6.1, qZn8.1, qZn8.2, qZn9.1, qZn12.1 Lu et al, 2008;Garcia-Oliveira et al, 2009;Ishikawa et al, 2010;Zhang et al, 2011;Anuradha et al, 2012;Jin et al, 2013;Swamy et al, 2018a;Swamy et al, 2018b;Dixit et al, 2019;Descalsota-Empleo et al, 2019;Calayugan et al, 2020;Lee et al, 2020;Pradhan et al, 2020 Iron (Fe) qFE-1, qFE-9, qGFe4, qSFe1, qSFe12, qFe1, qFe3, qFe6, qFe2-1, qFe9-1, qFe4.1, qFe3.3, qFe7.3, Fe8.1, qFe12.2, qFe3-1, qFe9.1, qFe12.1, qFe1.1, qFe1.2, qFe6.1, qFe6.2, qFe5, qK6.1, qFe2.2, qFe3.1, qFe4.1., qFe6.1, qFe8.1, qFe11.2, qFe11.3, qFe12.1, Stangoulis et al, 2007;Lu et al, 2008;Garcia-Oliveira et al, 2009;Ishikawa et al, 2010;Norton et al, 2010;Jin et al, 2013;Swamy et al, 2018a;Swamy et al, 2018b;Dixit et al, 2019;Calayugan et al, 2020;Lee et al, 2020;Pradhan et al, 2020 Zn andIron qZn10, qZn2, qZn4, qZn5, qZn6, qZn7, qZn9 Zhang et al, 2014 Manganese (Mn) qMn1-1, qMn2-1, qMn3-1, qMn10-1, qMn2.1, qMn2.1, qMn7.1, qMn1.1, qMn1.2, qMn3.1, qMn3.2, qMn4.1 -Oliveira et al, 2009;...…”
Section: Traitsmentioning
confidence: 99%